2022
DOI: 10.3389/fbioe.2022.968342
|View full text |Cite
|
Sign up to set email alerts
|

Microfluidics for long-term single-cell time-lapse microscopy: Advances and applications

Abstract: Cells are inherently dynamic, whether they are responding to environmental conditions or simply at equilibrium, with biomolecules constantly being made and destroyed. Due to their small volumes, the chemical reactions inside cells are stochastic, such that genetically identical cells display heterogeneous behaviors and gene expression profiles. Studying these dynamic processes is challenging, but the development of microfluidic methods enabling the tracking of individual prokaryotic cells with microscopy over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 136 publications
0
7
0
Order By: Relevance
“…We used a microfluidic device commonly called “mother machine” to follow growing and dividing cells for hundreds of generations in controlled environments [50, 51]. Single-cells are trapped in micrometer wide trenches.…”
Section: Methodsmentioning
confidence: 99%
“…We used a microfluidic device commonly called “mother machine” to follow growing and dividing cells for hundreds of generations in controlled environments [50, 51]. Single-cells are trapped in micrometer wide trenches.…”
Section: Methodsmentioning
confidence: 99%
“…This microfluidic platform has massively contributed to the recent advances in genetic circuits and understanding bacterial dynamics. 15,38 Zhang et al 15 have reported a genetic circuit resembling closely to the repressilator, with controlled amplitude and period. They use mVenus as the reporter gene regulated by a dual-input promoter and uses salicylate for inducing changes in amplitude and IPTG for period.…”
Section: Analyzing Bacterial Dynamics: Channel-based Microfluidic Pla...mentioning
confidence: 99%
“…These techniques can be used to create microscale channels and chambers for the microorganism to reside in. These microscale structures can be integrated with a transducer to produce a measurable signal [35]. Some commonly used microfabrication techniques in the fabricating microbial biosensors are:…”
Section: Microfabricationmentioning
confidence: 99%